Time Trend of Occupational Noise-induced Hearing Loss in a Metallurgical Plant With a Hearing Conservation Program - Adalva V. Couto Lopes; Cleide F. Teixeira; Mirella B.R. Vilela; Maria L.L.T. de Lima (Elsevier, 2024)
Background: This study aimed to analyze the trend of occupational noise-induced hearing loss (ONIHL) in Brazilian workers at a metallurgical plant with a hearing conservation program (HCP), which has been addressed in a previous study. Methods: All 152 workers in this time series (20032018) participated in the HCP and used personal protective equipment. All annual audiometry records in the company's software were collected from the electronic database. The trend of ONIHL was analyzed with the joinpoint regression model. The hearing thresholds of ONIHL cases at the end of the series were compared with those found in a national reference study. Results: The binaural mean hearing thresholds at 3, 4, and 6 kHz at the end of the series were higher for ages ≥50 years, exposures ≥85 dB (A), time since admission >20 years, and maintenance workers. Significance was found only in the group divided by age. There was an increasing time trend of ONIHL, though with a low percentage variation for the period (AAPC = 3.5%; p = 0.01). Hearing thresholds in this study differed from the reference one. Conclusion: Despite the unmet expectation of a stationary trend in the study period, the time pace of ONIHL evolution did not follow what was expected for a population exposed to noise. These findings signal to the scientific community and public authorities that good ONIHL control is possible when HCP is well implemented.